Conditions That Determine Changing the Function of Mine Shafts in a Gassy Coal Mine—A Case Study - Nikodem Szlązak; Marek Korzec (Energies, 2024)
Ventilation plays a key role in ensuring safe exploitation in underground gassy mines. Over the years, the structure of a mine’s ventilation network changes. Therefore, it becomes necessary to construct new excavations, while some existing excavations lose their potential for future mining activity. Constructing new excavations, especially shafts, is very expensive. Therefore, mine operators are looking for solutions to ensure appropriate ventilation by reorganizing the ventilation network and using existing infrastructure, including shafts. This article presents the example of a coal mine located in the Upper Silesian Coal Basin in Poland to discuss the factors relevant to switching the function of one of the central shafts from a downcast function to an upcast one. This change is accompanied by the closure of a peripheral upcast shaft. The main aim of this change is to assess the possibility of further safe operation without the construction of new shafts. This action also results in the release of the coal currently closed in the pillar of the shaft being closed. Using a numerical model of the mine ventilation network allowed for the comparison of the considered solutions before making final decisions and implementing changes in the network. The calculations showed that it is possible to provide appropriate ventilation in the mine, but it would need to take into account certain technological assumptions, like the additional technical function of the changed shaft. This article discusses the advantages and disadvantages of modifications to the mine ventilation network, as well as their guiding principles, in the context of existing methane hazards. The procedure presented in this article can be adopted in other mine ventilation networks in which analogous modifications are considered.